Design a Two-Axis Sensorless Solar Tracker Based on Real Time Clock Using MicroPython - Karisma Trinanda Putra; Ahmad Zaki Arrayyan; Ramadoni Zaki Syahputra; Yoga Agil Pamungkas; Mosiur Rahaman (Emerging Information Science and Technology, 2023)
Since the majority of the electrical energy required to meet consumer demands is still produced by the typical power plant using fossil fuels, the world's electricity supply will eventually approach a critical point due to the steady depletion of fossil fuels. One solution to replacing energy derived from fossil fuels is solar energy. However, the results of energy generation are significantly influenced by the angle of the solar panels to the direction of sunlight. Therefore, in order to optimize the production of electrical energy, a microcontroller system that can track sunlight is developed using MicroPython. This research calculated the azimuth angle and elevation angle to create a solar tracker that can follow the sun's position based on time. The results of this research reveal that solar trackers at 21.30 volts and rooftop solar panels at 20.44 volts when both produce open circuit voltage. With an solar tracker, solar panels may operate up to at a 20% efficiency in sunny conditions, compared to an average efficiency of 18% for rooftop solar panels.